1999
DOI: 10.1115/1.555373
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of the Initial Yielding Behavior of a Hard Coating/Substrate System With Functionally Graded Interface Under Indentation and Friction

Abstract: The initial yielding behavior due to the indentation and friction process between an elastic cylindrical surface and hard coating/functionally graded substrate system is analyzed by finite element modeling. A thin hard DLC film deposited on a soft Ti–6Al–4V alloy substrate is considered as a model system. Two functional gradient substrate conditions are considered: (i) a gradient in yield strength and (ii) a gradient in elastic modulus. In both cases, appropriate gradients result in significant benefits to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 27 publications
0
37
0
Order By: Relevance
“…Besides, Stephens et al (2000) investigated the initial yielding behavior in a hard coating/substrate system with functionally graded interface under frictional Hertzian contact based on the finite element modeling. It was indicated that the appropriate gradients in yield strength or elastic modulus could result in benefits to the reliability of the coated system compared to the case of an ungraded substrate.…”
Section: Article In Pressmentioning
confidence: 99%
“…Besides, Stephens et al (2000) investigated the initial yielding behavior in a hard coating/substrate system with functionally graded interface under frictional Hertzian contact based on the finite element modeling. It was indicated that the appropriate gradients in yield strength or elastic modulus could result in benefits to the reliability of the coated system compared to the case of an ungraded substrate.…”
Section: Article In Pressmentioning
confidence: 99%
“…Most recently, the multilayered approach was equally applied by Liu et al [19] in solving the axisymmetric frictionless contact problem of functionally graded materials. With the intention of providing some insights into the design of coatings, Stephens et al [20] performed a finite element analysis to investigate the initial yielding behavior in a hard coating/substrate system with functionally graded interface under the simplifying assumption of a frictional Hertzian contact pressure profile, indicating the beneficial influence of gradients in yield strength or elastic modulus on the reliability of the coated system. Additional results that address the contact response of graded materials on the basis of the aforementioned Hertzian pressure distribution are to be found in [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…They found that the stresses of both the outer surface of the coating and the coating-substrate interface are complicated functions of (a) the ratio of the Young moduli of the coating and substrate and (b) the ratio of the coating thickness to the contact halfwidth; and that the stresses which could be responsible for coating failure cannot simultaneously be minimized by appropriate choice of variable. Further, Stephens et al [63] analyzed initial yielding behavior due to the indentation and friction process between an elastic cylindrical surface and a hard coating/functionally graded substrate system where a thin hard DLC film deposited on a soft Ti-6Al-4V alloy substrate is considered as a model system with consideration of two functional gradient substrate conditions: (a) a gradient in yield strength and (b) a gradient in elastic modulus. They found that in both cases, appropriate gradients result in significant benefit to the reliability of the coated system, compared to the case of an ungraded substrate.…”
Section: Continuum Modelsmentioning
confidence: 99%